The Implementation of Praying Habit of Students' Religious Character at the Smart Learning Institution of Bandar Sribhawono - Swastini, Swastini; Jaenullah, Jaenullah; Syaifullah, Muhammd (International Journal on Advanced Science, Education, and Religion, 2025)
This study explores the role of prayer habits in shaping the religious character of students at the SMART Tutoring Institute in Bandar Sribhawono, East Lampung. Within the context of non-formal education, prayer serves as a key medium for cultivating religious values and character. Using a qualitative approach, this research employs observation, interviews, and documentation methods. The findings indicate that the practice of praying before and after study sessions positively contributes to the development of students' religious character, particularly in terms of patience, piety, gratitude, empathy, discipline, and responsibility. Beyond spiritual development, this habit also enhances social interactions among students and between students and teachers. Despite challenges—such as varying levels of focus during prayer and the diversity of students' religious backgrounds—the SMART Tutoring Institute has effectively integrated prayer into its activities in an adaptive manner. The implementation of this habit fosters a more conducive learning environment, promotes religious behavior, and contributes to improved academic performance. The study recommends that prayer be systematically incorporated into learning activities at non-formal educational institutions to help nurture a generation grounded in strong character and faith.